Biochemical and nutritional parameters of egresses in health area courses - Barbosa, Rafaela Miranda; Pereira, Lilian Rodrigues; Almeida, Jussara de Castro [UNESP]; Padua, Karina Maciel; Ribeiro, Maxwell Messias; Piantino, Camila Belfort (Inst Brasileiro Pesquisa & Ensino Fisiologia Exercicio-ibpefex, 2018)
In recent years we have observed an increase in the prevalence of overweight and obesity, making them one of the most important public health problems. The control of obesity/overweight constitutes an important goal, since it is associated with metabolic alterations. The objective of this study was to evaluate and compare the nutritional status and biochemical parameters of university students entering health courses. This is an observational cross-sectional study. The parameters evaluated were weight, IMC, % G, CA, triglycerides, total cholesterol and fasting glycemia. The collected data were analyzed in the open source software R (The R Foundation for StatisticalComputing (c)), version 2.5.1, Vegan package and the level of significance was alpha = 0.05. The dominant profile consists predominantly of female Biomedicine students with a mean age of 21.6 +/- 8.1 years. The mean weight observed was 64.6 +/- 10.2 kg, height of 1.7 +/- 0.06 m, mean BMI of 23.4 +/- 13.0 kg/m2 and % G of 27.7 +/- 7.8%. The biochemical parameters of the students remained, in a general context, within the values considered desirable, with average values of 183.5 +/- 42.1 mg/dL for cholesterol, 87.4 +/- 45.9 mg/dL for triglycerides and 77, 5 +/- 7.3 mg/dL for glycemia. It was evidenced that the majority of individuals presented normal nutritional and biochemical parameters.
Keywords: Obesity; Overweight; Blood Chemical Analysis